2019
DOI: 10.1108/jima-09-2017-0097
|View full text |Cite
|
Sign up to set email alerts
|

Informalshariahpawnshop in the traditional markets of Surakarta

Abstract: Purpose This study aims to explore how informal pawnbrokers and informal pawners interpret the existence of the informal pawnshop in the traditional market in Surakarta, Indonesia, with the main focus to determine the applicability of informal pawnshop development model. Design/methodology/approach The research used the qualitative method with the phenomenological approach using interview method to fully comprehend the informants’ views regarding the informal pawnshop existence in traditional markets in Sura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The findings of Goh et al (2017) also found that trade (dependent), FDI and GDP (independent) variables found the long cointegration among these variables. The findings of as Durairaj ( 2010), Shabbir (2019) and showed only on the bases of the significance of F 1 and found that there is the long run relationship exists between FDI and other variables.…”
Section: Resultsmentioning
confidence: 96%
“…The findings of Goh et al (2017) also found that trade (dependent), FDI and GDP (independent) variables found the long cointegration among these variables. The findings of as Durairaj ( 2010), Shabbir (2019) and showed only on the bases of the significance of F 1 and found that there is the long run relationship exists between FDI and other variables.…”
Section: Resultsmentioning
confidence: 96%
“…The qualitative research method is related to the collection of information about phenomenon and events and things that have occurred or existing recently (Sandewoloski, 2000). The researcher has chosen this method to describe and analyze a problematic concept about Islamic economics (Shabbir, 2018b;Shabbir, 2019). The researcher used the myriads of pedantries get at able from the vulnerable literature on Islamic economics, Western economics, past research papers, articles from available resources including research journals, online libraries, and magazines from different websites.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the question about the role of biradari, patronageclient relations for party positions and social networks, members highlighted their importance and impact on women's political participation (Shabbir, 2019). One member (city president) shared her views about the party attitude toward workers who do not have a strong linkage or support to come forward.…”
Section: Role Of Client/patronage Relationsmentioning
confidence: 99%